Tourism in the Era of Industry 4.0: Harnessing Digital Storytelling and Social Media for Effective Promotion - Stanss. L. H. V. Joyce Lapian; Silvya L. Mandey; Willem J. F. A. Tumbuan; Imelda W. J. Ogi; Darmawati Syam; Yaulie Rindengan; Yance Ambaho; Roberthair Suripatty; Winarsih Winarsih; Meiland Makalisang; Naomi Ormak (Univiversitas Dr. Djar Wattiheluw, 2025)
Digital technology has transformed tourism promotion, especially through digital marketing and storytelling. The COVID-19 pandemic accelerated the use of social media and e-commerce, with storytelling helping build emotional connections and improve destination images. In Indonesia, the Ministry of Tourism uses platforms like TikTok and Instagram for this purpose. Research in West Papua Barat Daya shows that short videos, photos, and blogs effectively raise awareness and attract tourists. Despite challenges like limited infrastructure and skills, digital storytelling remains a powerful and sustainable tool for tourism promotion.